2001
DOI: 10.1001/archneur.58.3.427
|View full text |Cite
|
Sign up to set email alerts
|

Open-Label, Multicenter, Phase 3 Extension Study of the Safety and Efficacy of Donepezil in Patients With Alzheimer Disease

Abstract: Donepezil is an effective and safe drug for the long-term symptomatic treatment of mild to moderately severe AD for up to 144 weeks (2.8 years), and sustained treatment may confer some advantages.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

15
224
2
4

Year Published

2002
2002
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 333 publications
(245 citation statements)
references
References 14 publications
15
224
2
4
Order By: Relevance
“…Data on the long-term use of donepezil comprise open-label extension studies of randomized, controlled trials (RCTs) [79][80][81] and placebo-controlled data for use up to 1 year. 82,83 Doody et al 79 presented results from 763 patients enrolled in a 144-week, open-label extension of 2 preceding RCTs.…”
Section: Long-term Symptomatic Efficacymentioning
confidence: 99%
See 2 more Smart Citations
“…Data on the long-term use of donepezil comprise open-label extension studies of randomized, controlled trials (RCTs) [79][80][81] and placebo-controlled data for use up to 1 year. 82,83 Doody et al 79 presented results from 763 patients enrolled in a 144-week, open-label extension of 2 preceding RCTs.…”
Section: Long-term Symptomatic Efficacymentioning
confidence: 99%
“…82,83 Doody et al 79 presented results from 763 patients enrolled in a 144-week, open-label extension of 2 preceding RCTs. The deterioration in the mean change from baseline of the Alzheimer's Disease Assessment Scale 84 cognitive subscale (ADAS-Cog: 0-70 points; higher scores ϭ impairment) was 7.4 to 9.1 points for the group that received 5 mg/d and 7.9 to 10.0 points for the group that received 10 mg/d, depending on the study.…”
Section: Long-term Symptomatic Efficacymentioning
confidence: 99%
See 1 more Smart Citation
“…More recently, it has been reported that acetylcholinesterase inhibitors as well as the muscarinic M 1 /M 4 preferring receptor agonist xanomeline reduce psychoticlike symptoms in patients with Alzheimer's disease (Bodick et al, 1997;Cummings, 2000;White and Cummings, 1996). Even though these newer compounds have considerably less parasympatomimetic side effects, nausea and vomiting have been reported in Alzheimer patients taking these drugs (Doody et al, 2001;Bodick et al, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…[29] The benefits of treatment with AChEIs are rapidly lost when drug administration is interrupted for as little as 6 weeks and may not be fully regained when drug treatment is reinstated. [30] Notwithstanding, it may be necessary to check whether the medication is having the desired effect by very occasionally withholding treatment for approximately 2 weeks when the recurrence in severity of former NPS/behavioural and psychological symptoms of dementia (BPSD) target symptoms will act as an indicator for continued treatment. [26] At least two-thirds of patients can be expected to derive modest benefit from the above medications with regard to not only improvement in cognition, but also to NPS/BPSD and activities of daily living (ADL).…”
Section: Pharmacological Treatment 431 Acetylcholinesterase Inhibitmentioning
confidence: 99%